The Sericini (Coleoptera: Scarabaeidae: Sericinae) from the Nanling Mountains, China - Li, Wei; Yang, Zhi-Yu; Liu, Wan-Gang; Ahrens, Dirk; Zheng, Ying-Juan; Bai, Ming; Liu, Yang (Zootaxa, 2024)
In this paper we update the knowledge on the species of Sericini occurring in the Nanling Mountains, China. This includes new records of 19 known species. Furthermore, six new species are described: Maladera paradaanensis Liu, Ahrens, Li & Yang, new species, M. tianqiae Liu, Ahrens, Li & Yang, new species, Neoserica (s. str.) parajingangshanica Liu, Ahrens, Li & Yang, new species, Tetraserica dabuensis Liu, Ahrens, Li & Yang, new species, Trioserica shimen Liu, Ahrens, Li & Yang, new species, and Lasioserica siyuanae Liu, Ahrens, Li & Yang, new species. The habitus and male genitalia of the new species are illustrated, and a map shows the distribution of the new species.